TELAAH KRITIS TERHADAP SYAZ SEBAGAI UNSUR KAEDAH KESAHIHAN MATAN HADIS - Mahsyar Idris (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2019)
Syaz as the principle to detect the validitiy of the content of prophetic tradition (hadis) has two major elements: isolation and opposite meaning. The development of major principle of syaz can be formulated into four minor principles: the hadis does not contradict the Qur’an; does not contravene the more valid hadis; does not opposite to the ijma’ (agreement of the prophet’s companions); and does not contradict the highly accurate reason that manages to detect the authenticity of hadis associated with the prophet. The scholars of hadis seem to be very careful in implementing the principle of ghayru syudzudz. This attitude is evident in the strict category in classifying a hadis as syudzudz. Researches on the syaz of hadis have clear methods and procedures. When these methods and procedures are applied consistently, there will be no discrepancy between the validity of sanad (chain) and matn (content).